PANEL DATA ANALYSIS OF ASIAN ECONOMIC CRISIS FROM MONETARY AND FISCAL POLICY POINT OF VIEW - Adianski, Azra; Noveria, Ana (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The Asian Economic Crisis of 1997–1998 stands as one of the most significant financial crises in the modern economic history. This research aims to revisit the Asian Economic Crisis through the dual frameworks of monetary and fiscal policy by applying a quantitative panel data methodology to assess the interactions between monetary and fiscal policy tools and key macroeconomic indicators across selected East and Southeast Asian economies.This study is motivated by the scientific need to understand how macroeconomic policy coordination shaped the trajectory of the crisis and its aftermath. This research applies a panel data regression model covering eight Asian countries including Indonesia, Thailand, South Korea, Malaysia, Philippines, Singapore, Hong Kong, and Japan during the period of 1995 to 2005.The study operates under a set of theoretical propositions grounded in monetary theory, fiscal theory, and business cycle theory. The hypothesis explores whether the monetary and fiscal policy has anything to do with the Asian Economic Crisis taking the role as the cause or the means of crisis mitigation. This proposition is tested using macroeconomic panel data indicators such as interest rates, M2 aggregates, inflation, exchange rates, government spending, taxation, and current account balances, analyzed through fixed and common effect regression models. Beyond its empirical contributions, the study also offers theoretical implications by revisiting key assumptions in monetary and fiscal theory in the context of open economies subject to volatile capital flows. The findings underscore the importance of institutional strength, policy credibility, and adaptive governance in managing macroeconomic crises. In summary, this research not only provides empirical validation for prevailing macroeconomic theories but also offers practical policy insights into how fiscal and monetary tools can be effectively coordinated in times of systemic crisis. Its contribution to science lies in its integrated methodological approach, its regionally comparative lens, and its relevance for contemporary policy challenges in an era of growing financial interconnectedness.